2006
DOI: 10.1364/oe.14.006297
|View full text |Cite
|
Sign up to set email alerts
|

Core-shell diamond-like silicon photonic crystals from 3D polymer templates created by holographic lithography

Abstract: . Core-shell diamond-like silicon photonic crystals from 3D polymer templates created by holographic lithography. Retrieved from http://repository.upenn.edu/mse_papers/89Core-shell diamond-like silicon photonic crystals from 3D polymer templates created by holographic lithography AbstractWe have fabricated diamond-like silicon photonic crystals through a sequential silica/silicon chemical vapor deposition (CVD) process from the corresponding polymer templates photopatterned by holographic lithography. Core-she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
61
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 16 publications
1
61
0
Order By: Relevance
“…[12] Using the previously developed two-parameter level surface we found that the pinch-off occurred at filling fraction of 20%, resulting in no complete photonic bandgap between 2nd and 3rd bands. [12] While searching for an appropriate parallel level surface of the diamond-like structure to more accurately study the pinch-off characteristics, we found that a simple combination a diamondlike level surface with a P level surface, in the same way as we did with D structure, did not represent a parallel surface of the diamond-like structure. Thus, we constructed the surface at the pinch-off by the points with the same distance from the template surface.…”
Section: G G =F G -C(cos(2x)cos(2y)+cos(2y)cos(2z)+cos(2z)cos(2x))=t mentioning
confidence: 94%
See 4 more Smart Citations
“…[12] Using the previously developed two-parameter level surface we found that the pinch-off occurred at filling fraction of 20%, resulting in no complete photonic bandgap between 2nd and 3rd bands. [12] While searching for an appropriate parallel level surface of the diamond-like structure to more accurately study the pinch-off characteristics, we found that a simple combination a diamondlike level surface with a P level surface, in the same way as we did with D structure, did not represent a parallel surface of the diamond-like structure. Thus, we constructed the surface at the pinch-off by the points with the same distance from the template surface.…”
Section: G G =F G -C(cos(2x)cos(2y)+cos(2y)cos(2z)+cos(2z)cos(2x))=t mentioning
confidence: 94%
“…To validate the model that approximates the grown layers using a parallel surface and investigate the effect of incomplete filling on the photonic bandgap properties, we chose a three-term diamond-like structure, which has similar symmetry to the fourterm diamond D structure. More importantly, both the polymer template and its inorganic replica of the three-term diamond-like structures can be fabricated rather conveniently [12] , in contrast to the fabrication of P, G, and D structures by holographic patterning. As seen in Fig.…”
Section: G G =F G -C(cos(2x)cos(2y)+cos(2y)cos(2z)+cos(2z)cos(2x))=t mentioning
confidence: 99%
See 3 more Smart Citations